Terahertz metamaterials application in sensing - MINAH SEO; Lee, Sang-Hun (한국물리학회, 2019)
Metamaterials, which were recently invented as artificial atomic structures with specific dielectric properties that do not exist in nature, can be applied to terahertz (THz) electromagnetic wave regime. Studies of such metamaterials have been actively carried out to improve the performance of the existing THz spectrometry. In this abstract, we will introduce detailed information on how to implement a highly sensitive and selective THz sensing method by optimizing sensitivity using nanoscale metamaterials while utilizing the unique molecular recognition characteristics of the terahertz spectroscopy. THz metamaterials here can be designed to match the desired resonance frequency to the target biochemical molecules, using the geometry of unit atomic structures including materials, thickness, length, or width. By doing so, it is expected that trace amounts such as small molecules, viruses, and proteins can be detected and sensing harmful gases will also be possible.